ANALISIS PENGARUH INBOUND TOURISM DAN INFRASTRUKTUR JALAN TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA - Firman Aris Irvannullah; Aisah Jumiati; Fajar Wahyu Prianto (Growth, 2018)
Economic growth is one of the benchmarks of country’s economic success. To improve the economy, one of them can be done by developing the tourism sector. This study aims to analyze the impact of inbound tourism and roadway infrastructure on economic growth as well as analyze the response of economic growth due to shock to variables inbound tourism and roadway infrastructure in Indonesia during the period 1984-2016. The method used in the research is vector autoregression (VAR). The results showed that in long-term tourist arrivals, tourism receipts, and roadway infrastructure significantly influence economic growth, but in the short-term only tourism receipts and roadway infrastructure are significantly influential. In the long-term tourist arrival and tourism receipts have a positive effect while the roadway infrastructure has a negative effect. Furthermore, in the short-term tourism receipts have a negative effect and roadway infrastructure has a positive effect on economic growth. Then, tourist arrivals and roadway infrastructure don’t have a causal relationship with economic growth, but there is a direct causal relationship of tourism receipts to economic growth. Impuls response function shows that PDB responds negatively to shocks that occur in inbound tourism, while a positive respons is indicated by PDB in case of shock to roadway infrastruktur.